Harnessing de novo transcriptome sequencing to identify and characterize genes regulating carbohydrate biosynthesis pathways in Salvia guaranitica L. - Abbas, Zahid Khorshid; Al-Huqail, Arwa Abdulkreem; Abdel Kawy, Aesha H.; Abdulhai, Rabab A.; Albalawi, Doha A.; AlShaqhaa, Manal Abdullah; Alsubeie, Moodi Saham; Darwish, Doaa Bahaa Eldin; Abdelhameed, Ahmed Ali; Soudy, Fathia A.; Makki, Rania M.; Aljabri, Maha; et al. (Frontiers in Plant Science, 2024)
Carbohydrate compounds serve multifaceted roles, from energy sources to stress protectants, found across diverse organisms including bacteria, fungi, and plants. Despite this broad importance, the molecular genetic framework underlying carbohydrate biosynthesis pathways, such as starch, sucrose, and glycolysis/gluconeogenesis in Salvia guaranitica, remains largely unexplored. In this study, Illumina-HiSeq 2500 platform revealed the transcripts of S. guaranitica leaves, generating approximately 8.2 Gb of raw data. Following data filtering and adapter sequence removal, 38 million reads comprising 210 million high-quality nucleotide bases were obtained. The de novo assembly yielded 75,100 unigenes, which were annotated to establish a comprehensive database for investigating starch, sucrose, and glycolysis biosynthesis. Within these, 410 unigenes were identified as putatively involved in these metabolic pathways, including 175 related to glycolysis/gluconeogenesis and 235 to starch and sucrose biosynthesis. Furthermore, functional analyses of glucose-6-phosphate isomerase (SgGPI), trehalose-6-phosphate synthase/phosphatase (SgT6PS), and sucrose synthase (SgSUS) in starch, sucrose, and glycolysis biosynthesis were conducted using transgenic Arabidopsis thaliana. Overexpression of these genes in transgenic A. thaliana enhanced leaf area, accelerated flower formation, and overall growth compared to the wild type plants. These findings lay a foundation for understanding the roles of starch, sucrose, and glycolysis biosynthesis genes in S. guaranitica, offering insights into future metabolic engineering strategies for enhancing the production of valuable carbohydrate compounds in either S. guaranitica or other plants.